Limitations of Technical Inputs in Small Scale Stone Quarrying in Kabale Municipality, Uganda. - Ahimbisibwe, Rosette (Kabale University, 2023)
The study was limited to limitations of technical inputs in small stone quarrying in Kiyoora Kabale municipality Kabale district, to identify the challenges faced by participants small scale stone quarrying, to suggest possible interventions to help improve small scale stone quarrying. The researcher employed a descriptive study design. A case a mixed approach was used. The study engaged a total population of 20 respondents from the study area. the study findings revealed that Quarrying is a very important activity in human life as it helps in the development of infrastructure such as roads in a given area, a huge supporter of local economic development since it enhances trade, creates jobs for people, creates new habitats where sometimes new roads are built and most people at quarrying site wholly depend on these quarrying for their livelihoods aside from other economic activities. the study recommended that There should be carefully pre-planning of the project to ensure that the quarrying process takes place well and in its actual. state because when this one is done, then the activity also goes on well to facilitate the desires of the community.